The Use and Abuse of Jus Nexi - Novogrodsky, Noah (Les ateliers de l'éthique / The Ethics Forum, 2012)
This paper uses Shachar’s conception of jus nexi to explore three interrelated ideas. I first contend that Shachar’s analysis of the monetary value of birthright citizenship may be applied to temporary workers, lawful permanent residents and naturalized citizens as an exposé of inherited privilege in diverse communities and as a means of identifying which forms of membership and belonging are worth owning. Second, I use the idea of jus nexi to question which additional work relationships and identity networks that might qualify as genuine connections to a given state. Finally, I question whether an operationalized version of jus nexi, that is an alternative category of citizenship, would supplant or complement existing jus soli and jus sanguinis rules. Here, I seek to apply Shachar’s theoretical contributions to current political debates and warn that a genuine connection test is increasingly being misused to support a nativist agenda.